Temporal assortment of cooperators in the spatial prisoner’s dilemma - Tim Johnson (Nature Portfolio, 2021)
Johnson and Smirnov show that temporal dynamics influence cooperation in the spatial prisoner’s dilemma. Studying simulation models, they find that when evolutionary selection operates on the time at which individuals socially interact, cooperation evolves at a wider range of parameter values than in standard spatial prisoner’s dilemma models.